Key Trends in Implementing the FUND's Transparency Policy. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2021)
At the time of the 2005 Review of the Fund's Transparency Policy, the Executive Board required regular updates on trends in implementing the transparency policy. This report provides an overview of recent developments, reflecting information on documents considered by the Board in 2019 and their respective publication status up to June 2020, and updating the previous annual report on Key Trends.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; Monetary Policy; Political Economy